India : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper evaluates corporate and banking sector vulnerabilities in India. The analysis shows that while corporate sector risks have subsided, debt repayment capacity remains strained, and high leverage continues to weigh on corporate resilience, which may pose further risks to banks' asset quality. Public sector banks have stepped up recognition of nonperforming assets, but their debt recovery capacity remains weak. Simulations suggest that potential recapitalization needs, at current provisioning levels, should have a modest fiscal impact.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet